Annelida. Polychaeta Sedentaria. - Berkeley, Edith; Berkeley, Cyril (Canadian Pacific Fauna. Fisheries Research Board of Canada, Toronto, 1952)
[Introduction as:] The Polychaeta Sedentaria differ from the Errantia (described in Part 1) chiefly in the following particulars. The body is often divided into two or more distinct regions. The head is frequently obscure or profoundly modified. The peristomium is usually apodous and achaetous. The parapodia are never prominent and generally inconspicuous though their lobes may be prolonged into lamellae or cirrus-like processes. The parapodia are nearly always biramous, but the rami are frequently marked by little more than setigerous areas. The ventral rami are often in the form of tori or pinnules armed with crotchets or with uncini. The proboscis is never armed. The Sedentaria are frequently tubiculous. The warning given in Part 1a bout using size, markings and coloration as characteristics for the determination of species applies equally, or even more strongly, in the case of the Sedentaria. The keys given below are designated to apply only to the families, genera and species dealt with. many of the illustrations are taken from Fauvel's volume in the "Faune de France", Vol. 16, "Polychètes Sédentaires". Others are taken from various papers to which reference is made in the text. Again we wish to acknowledge our indebtedness to the authors of the publications concerned. Finally, we wish to pay tribute to the memory of Mr. E. F. Ricketts, formerly of Pacific Grove, California, to whose enthusiasm for shore collecting many of our records are due.
World Polychaeta Database (WPolyDb)